ADVANTAGES AND DISADVANTAGES OF ADVERTISING BY SOCIAL NETWORKS - Simić, Nataša; Petrović, Vesna; Aničić, Dušan (Journal of process management and new technologies, 2019)
Global technological progress has significantly affected public relations. New communication technologies have enabled creation of competent markets. Development of modern technology affected the production of the so-called personal products which have been created based on knowledge of consumer demands and needs. Pursuant to that, the communication is based on two-sidedness, and the central point of interactive public relations is taken by communication model "one on one" and "many to many", instead of the communication model which is directed toward masses, where the dominant direction is "one to many". There is a high degree of consent on the role and significance of social networks at all levels, starting from the global corporate success to resolution of daily problems of individuals. One of the most important problems is the safety of companies’ appearance in the cyber space. This paper is supposed to point out to the advantages, as well as dangers with which companies face when conquering their "piece" of cyber space.